COVID-19, mobility restriction, and sexual behavior among a cohort of people of reproductive age: Nigeria - Adekola, Paul O.; Ugwu, Favour C.; Amoo, Emmanuel O.; Olawole-Isaac, Adebanke; Cirella, Giuseppe T. (Frontiers in Public Health, 2023)
Background: Non-pharmaceutical strategies adopted by various governments to control the spread of COVID-19 is through mobility restriction (MR), popularly known as a lockdown. Evidence shows that MR has some unintended consequences that increased cases of domestic violence, rape, pornography, sex chats, incest, and other unhealthy sexual behaviors (SBs). Methods: The study examined the influence of MR on SB in Owerri via a cross-sectional quantitative approach. A total of 425 interviews were randomly administered among reproductive aged people. Data were analyzed using univariate, bivariate, and multivariate levels of analysis. Results: Results revealed that a significant relationship exist between selected socio-demographic characteristics such as age and marital status and their ability to cope with sexual abstinence. Results from the logistic regression analysis further illustrated this observation since during MR people were twice as likely to engage in prolific sex chats that could spur other harmful SB. Conclusion: It is recommended that people should be given privilege to determine whether they would like to stay with each other in subsequent lockdowns, or otherwise, to prevent some of the unpleasant SBs recorded.